1995
DOI: 10.1007/bf01276506
|View full text |Cite
|
Sign up to set email alerts
|

Phencyclidine-induced increases in striatal neuron firing in behaving rats: reversal by haloperidol and clozapine

Abstract: Amphetamine and related drugs of abuse facilitate dopamine transmission in the striatum. This action is believed to underlie the increase in firing of striatal motor-related neurons after amphetamine administration in behaving rats. The present study extended this electrophysiological investigation to phencyclidine (PCP), a nonamphetamine psychomotor stimulant that acts primarily as a noncompetitive antagonist of N-methyl-D-aspartate (NMDA) glutamate receptors. Like amphetamine, PCP (1.0, 2.5, or 5.0 mg/kg) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 55 publications
4
12
0
Order By: Relevance
“…In our studies, a possible mechanism by which these clinically effective antipsychotic agents attenuated the acute inhibitory effects of dizocilpine on miR-219 concentrations is by decreasing the neurochemical and behavioral deficits associated with NMDA receptor hypofunction. Consistent with this hypothesis, it has been shown that haloperidol and clozapine can facilitate NMDA receptor function (44) and counter the inhibitory effects of dizocilpine on NMDA receptor-mediated transmission (45).…”
Section: Discussionsupporting
confidence: 58%
“…In our studies, a possible mechanism by which these clinically effective antipsychotic agents attenuated the acute inhibitory effects of dizocilpine on miR-219 concentrations is by decreasing the neurochemical and behavioral deficits associated with NMDA receptor hypofunction. Consistent with this hypothesis, it has been shown that haloperidol and clozapine can facilitate NMDA receptor function (44) and counter the inhibitory effects of dizocilpine on NMDA receptor-mediated transmission (45).…”
Section: Discussionsupporting
confidence: 58%
“…However, deletion of D2Rs in the STR attenuated the PCP response ( Fig. 3B) compared with controls (Ps < 0.01), consistent with striatal D2R antagonism inhibiting PCP-mediated responses (49,50). These pharmacological and behavioral data suggest distinct roles for D2R signaling in the PFC versus the STR in mediating antipsychotic-like effects.…”
Section: Distinct Striatal Vs Cortical Role Of D2r On Pcp-mediated Bsupporting
confidence: 65%
“…Although D2R PFC agonism inhibits PCP-induced locomotion, striatal D2R antagonism is thought to be the primary mechanism of action of most APDs (49,50). To broadly explore this paradoxical role of D2R function behaviorally, we selectively deleted D2Rs in either the PFC by injecting an mCherry-Cre adeno-associated virus (AAV) in the previously described D2R floxed (D2 f/f ) mice (51) or the STR by crossing D2 f/f mice with adenosine 2A receptor Cre (A2aCre) mice (Fig.…”
Section: Distinct Striatal Vs Cortical Role Of D2r On Pcp-mediated Bmentioning
confidence: 99%
“…Thus, inhibitory effects of NMDA antagonists on striatal dopamine release may not be mediated locally within striatum but may require intact striatonigral circuitry. In support of this hypothesis, PCP and MK-801 have both been shown to increase the firing rate of nigrostriatal neurons, an effect that would lead to enhanced striatal dopamine release (White et al 1995).…”
Section: Discussionmentioning
confidence: 88%